Appendicular Tuberculosis as Manifestation of Gastrointestinal Tuberculosis: A Case Report - Yuliza Yuliza; Alfian Nur Rosyid; Wiwin Is Effendi; Prastuti Asta Wulaningrum; Herley Windo Setiawan (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Gastrointestinal tuberculosis (GI TB) is quite rare with 3% incidence of all extrapulmonary involvement. Appendicular TB may occur in 0.1 - 3% of cases. Diagnosis is often difficult because the patient usually complains about chronic abdominal pain and fever. A definite diagnosis is based on histopathological examination of resected specimens from the appendectomy procedure.Case: We present a 37-year-old male patient admitted to the hospital with chronic abdominal pain, fever, nausea, and loss of body weight. The patient never had a persistent cough, hemoptysis, or night sweating. Physical examination showed pain and muscular rigidity in the right iliac area during palpation with Blumberg's sign and Rovsing's sign positive. Abdomen ultrasound imaging showed an appendicular abscess. The patient underwent appendectomy afterwards with histopathology result showing TB. The patient was treated with first category anti-tuberculosis drugs (ATD).Discussion: Diagnosis of appendicular TB is difficult due to unspecific clinical presentations. Appendicular TB patients often complain of signs and symptoms which are similar to acute appendicitis. These conditions can delay ATD treatment because the definitive diagnosis could be made after histopathological examination.Summary: Appendicular TB is a rare case of extrapulmonary TB. It can present as acute appendicitis. The definitive diagnosis is based on the histopathological examination. It is recommended to check the appendicectomy specimens histopathologically to exclude TB or other diseases.